Analysis of relations between “equality of life chances” and “early childhood care and education”, as foundations for social justice and human development: a case study of Mauritius - Morabito, Christian (Afrika Focus, 2016)
In this research, we have analysed the relations between equality of life chances and early childhood care and education (ECCE). During the last decades we have seen a constant growth in socio-economic inequalities world-wide. Yet, in the same period, we have acknowledged an increasing attention, among scholars and policy makers, to early childhood education as a prominent (and consensual) equalizing policy. We critically reviewed this claim, by using a mixed method research, including a theoretical analysis through a critical literature review, quantitative analyses of a longitudinal database, and qualitative focus groups with parents in Mauritius. Findings suggest ECCE can only be an equaliser if accompanied by a change in the educational and social structures. Conclusions highlight the need of focusing further research on detecting complex mechanisms of accumulation of disadvantage in specific groups, and assessing the equalising effects of diverse interventions during early years, including income redistribution. Key words: equality, education, early childhood, Mauritius